Development and Validation of UV-spectrophotometric Method for Estimation of Berberine Hydrochloride in Marketed Formulation and Poly Lactic Co-glycolic Acid Nanoparticles - Tavade, Snehal; Patil, Kalpana; Kurangi, Bhaskar; Suryawanshi, Shailendra (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: The objective of present investigation is to develop and validate UV-Spectrophotometric method for estimation of Berberine hydrochloride in marketed formulation and Poly lactic co glycolic acid nanoparticles. Materials and Methods: Methanol was used for the development of UV-Spectrophotometric method. Berberine hydrochloride was detected using a 422nm wavelength. According to ICH requirements, the developed method was validated in terms of, selectivity, linear range, precision, robustness, ruggedness, and reproducibility. The developed method was further successfully used to estimate berberine hydrochloride in marketed formulations and poly lactic co glycolic acid nanoparticles. Results: Berberine hydrochloride has a maximum absorption wavelength of 422nm. Beer’s law was followed at concentrations ranging from10-50μg/ml. The limit of detection and limit of quantification were found to 2.81μg/ ml and 8.54μg/ml respectively. The precision and repeatability scores were all within acceptable limits. Berberine hydrochloride recovery in marketed formulations was found to be between 100-105%. The precision and repeatability values were within a 2% tolerance range. Berberine hydrochloride was found to have a purity of 92.27 %. Conclusion: The method was found to be easy, environmentally friendly, repeatable, and cost-effective, and it can be used for Berberine hydrochloride analysis on a regular basis.
Keywords: Berberine HCl; Beer’s law; Methanol; Water; Validation; Poly lactic; co-glycolic acid nanoparticles